2006
DOI: 10.3171/jns.2006.104.6.974
|View full text |Cite
|
Sign up to set email alerts
|

Microcatheter pull-up technique in the transvenous embolization of an isolated sinus dural arteriovenous fistula

Abstract: The authors describe a novel technique involving the use of a gooseneck snare for microcatheterization of isolated sinus dural arteriovenous fistulas (DAVFs). In some patients the inferior petrosal and transverse-sigmoid sinuses, the route of transvenous embolization (TVE) for DAVF, are separated by several channels. Even if a guidewire can be passed over the occluded portion and the affected sinus can be accessed, one may not necessarily be able to insert a microcatheter. The authors report on three patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Variations of the technique described by Gobin et al 32 and Naito et al, 29 which was used in our series, were reported by Hanaoka et al, 34 who used a snare to pull a microcatheter up into the occluded sinus in 3 patients, and by Halbach et al 35 and Komiyama et al, 27 who gained access to the isolated sinus from the contralateral side. The latter approach may necessitate the use of a triaxial system to provide better support.…”
Section: Discussionmentioning
confidence: 70%
“…Variations of the technique described by Gobin et al 32 and Naito et al, 29 which was used in our series, were reported by Hanaoka et al, 34 who used a snare to pull a microcatheter up into the occluded sinus in 3 patients, and by Halbach et al 35 and Komiyama et al, 27 who gained access to the isolated sinus from the contralateral side. The latter approach may necessitate the use of a triaxial system to provide better support.…”
Section: Discussionmentioning
confidence: 70%
“…In cerebrovascular procedures, however, most reports utilizing the Snare system have been cases involving retrieval of intravascular foreign bodies and treatment devices like coils and stents. Hanaoka et al reported their experiences of using the Snare system to intravenously catch the microcatheter in treating a dural arteriovenous fistula 19 . To our knowledge, this is the first report in English describing the use of the Snare system…”
Section: Resultsmentioning
confidence: 99%
“…However, TAE is selected for the treatment of iDAVF accompanied by cortical venous reflux because direct surgery is invasive and TVE is difficult to obtain the access to affected venous sinus. 2,5,6) Although NBCA has been used as an embolic material for TAE, the complete occlusion rate was 33%-56%, 7,8) which was not satisfactory. Recently, there have been a number of reports transarterial embolization of the left occipital artery and ascending pharyngeal artery using NBCA and particles, she was transferred to our hospital.…”
Section: Discussionmentioning
confidence: 99%